Mechanomedicine: Present state and future promise - Ning Wang; Shu Chien; Martin A. Schwartz (Proceedings of the National Academy of Sciences, 2025)
Two recent conferences on mechanotransduction in biology and medicine showcased remarkable progress in this field and the potential for bringing mechanobiology into the clinic. In this Perspective, we discuss recent advances, the conceptual frameworks needed to develop clinical tools based on mechanobiology, and prospects for the future.